Study on the Efficiency Treatment of Polluted Water by Biofilm Process Filled with Bamboo Filler - Hong, Qiankun; Zhang, Hangli; Zhang , Shixia (Strategic Planning for Energy and the Environment, 2022)
The biofilm process has the advantages of strong load impact resistance, low power consumption, easy operation and management, and good treatment effect. The key factor of the biofilm method is the biofilm carrier filler. The performance of the filler will directly affect the operation and treatment effect of the reactor. Aiming at the severely polluted rivers, this paper proposes to use bamboo materials with extensive raw materials, cheap processing, green and pollution-free materials to make biofilm reactor fillers, and conduct laboratory-scale research on them. The results show that, compared with the suspended filler, the bamboo filler has a faster filming speed and a rich microbial population structure on the film, which is beneficial to the removal of pollutants in the water. In addition, the bamboo filler has a degradable carbon source, which helps to further improve the reactor. The denitrification efficiency. The research results will provide technical support for the practical application of bamboo fillers in biofilm reactors and the in-situ remediation of polluted river water quality in my country.